κ-Opioid Regulation of Neuronal Activity in the Rat Supraoptic Nucleus In Vivo - Brown, Colin H. (J Neurosci, 1998)
We investigated the influence of endogenous κ-opioids on the activity of supraoptic neurons in vivo. Administration of the κ-antagonist nor-binaltorphimine (200 μg/kg, i.v.), increased the activity of phasic (vasopressin), but not continuously active (oxytocin), supraoptic neurons by increasing burst duration (by 69 ± 24%) and decreasing the interburst interval (by 19 ± 11%). Similarly, retrodialysis ofnor-binaltorphimine onto the supraoptic nucleus increased the burst duration (119 ± 57% increase) of vasopressin cells but did not alter the firing rate of oxytocin cells (4 ± 8% decrease). Thus, an endogenous κ-agonist modulates vasopressin cell activity by an action within the supraoptic nucleus. To eliminate κ-agonist actions within the supraoptic nucleus, we infused the κ-agonist U50,488H (2.5 μg/hr at 0.5 μg/hr) into one supraoptic nucleus over 5 d to locally downregulate κ-receptor function. Such infusions reduced the spontaneous activity of vasopressin but not oxytocin cells and reduced the proportion of cells displaying spontaneous phasic activity from 26% in vehicle-infused nuclei to 3% in U50,488H-infused nuclei; this treatment also prevented acute inhibition of both vasopressin and oxytocin cells by U50,488H (1000 μg/kg, i.v.), confirming functional κ-receptor downregulation. In U50,488H-infused supraoptic nuclei, vasopressin cell firing rate was increased by nor-binaltorphimine (100 and 200 μg/kg, i.v.) but not to beyond that found in vehicle-treated nuclei, indicating that these cells were not U50,488H-dependent. Thus, normally functioning κ-opioid mechanisms on vasopressin cells are essential for the expression of phasic firing.